2014
DOI: 10.1161/circinterventions.113.000659
|View full text |Cite
|
Sign up to set email alerts
|

Low Coronary Microcirculatory Resistance Associated With Profound Hypotension During Intravenous Adenosine Infusion

Abstract: Background-Intravenous adenosine infusion produces coronary and systemic vasodilatation, generally leading to systemic hypotension. However, adenosine-induced hypotension during stable hyperemia is heterogeneous, and its relevance to coronary stenoses assessment with fractional flow reserve (FFR) remains largely unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…In such scenarios, high-dose intravenous administration of adenosine may lead to false-positive FFR results in addition to an acute and undesirable deterioration in haemodynamics. 42 When making an assessment in the acute setting, the potential for such undesirable deterioration should always be considered, especially when there is a large myocardial mass and depressed LV function is involved.…”
Section: Potential Limitations Of Ffr In Acsmentioning
confidence: 99%
See 1 more Smart Citation
“…In such scenarios, high-dose intravenous administration of adenosine may lead to false-positive FFR results in addition to an acute and undesirable deterioration in haemodynamics. 42 When making an assessment in the acute setting, the potential for such undesirable deterioration should always be considered, especially when there is a large myocardial mass and depressed LV function is involved.…”
Section: Potential Limitations Of Ffr In Acsmentioning
confidence: 99%
“…ACS, acute coronary syndrome; CAD, coronary artery disease; FFR, fractional flow reserve; iFR, instantaneous wave-free ratio. (Adapted from Echavarría-Pinto et al) 42. …”
mentioning
confidence: 99%
“…However, Echavarria-Pinto et al reported a relationship between obesity (defined as body mass index ≥30 kg/ m 2 ), lower IMR corr values, and more frequent hypotensive responses to intravenous adenosine infusion in 79 patients with intermediate stenosis. 23 Likewise, there have been controversies whether common cardiovascular risk factors which have been known to cause macrovascular disease are also risk factors for primary microvascular disease. 24 In our results, conventional risk factors of macrovascular disease, as well as stenosis severity of epicardial coronary stenosis, were not associated with high IMR.…”
Section: Determinants Of High Imrmentioning
confidence: 99%
“…Previous research from our group [8] has suggested a more profound vasodilatory effect of adenosine on the microcirculation in patients with obesity and diabetes; these patients may have a greater protective benefit from Ticagrelor during PCI.…”
Section: Rationalementioning
confidence: 99%
“…Additionally, previous research [8] has identified a more pronounced effect of adenosine on microcirculatory resistance in patients with obesity and diabetes. Therefore, a potentially higher protective effect of Ticagrelor during PCI might be expected in this subgroup.…”
Section: Introductionmentioning
confidence: 99%